Concussions and Head Injuries in English Community Rugby Union Match Play. (February 2017) - Roberts, Simon P.; Trewartha, Grant; England, Michael; Goodison, William; Stokes, Keith A.
Background: Previous research has described general injury patterns in community-level rugby union, but specific information on time-loss head injuries has not been reported. Purpose: To establish the incidence and nature of significant time-loss head injuries in English community rugby match play, and to identify the injury risk for specific contact events. Study Design: Descriptive epidemiology study. Methods: Over 6 seasons, injury information was collected from 46 (2009-2010), 67 (2010-2011), 76 (2011-2012), 50 (2012-2013), 67 (2013-2014), and 58 (2014-2015) English community rugby clubs (Rugby Football Union levels 3-9) over a total of 175, 940 hours of player match exposure. Club injury management staff reported information for all head injuries sustained during match play whereby the player was absent for 8 days or greater. Clubs were subdivided into semiprofessional (mean player age, 24.6 ± 4.7 years), amateur (24.9 ± 5.1 years), and recreational (25.6 ± 6.1 years) playing levels. Contact events from a sample of 30 matches filmed over seasons 2009-2010, 2010-2011, and 2011-2012 provided mean values for the frequency of contact events. Results: The overall incidence for time-loss head injuries was 2.43 injuries per 1000 player match hours, with a higher incidence for the amateur (2.78; 95% CI, 2.37-3.20) compared with recreational (2.20; 95% CI, 1.86-2.53) ( P = .032) playing level but not different to the semiprofessional (2.31; 95% CI, 1.83-2.79) playing level. Concussion was the most common time-loss head injury, with 1.46 per 1000 player match hours. The tackle event was associated with 64% of all head injuries and 74% of all concussions. There was also a higher risk of injuries per tackle (0.33 per 1000 events; 95% CI, 0.30-0.37) compared with all other contact events. Conclusion: Concussion was the most common head injury diagnosis, although it is likely that this injury was underreported. Continuing education programs for medical staff and players are essential for the improved identification and management of these injuries. With the majority of head injuries occurring during a tackle, an improved technique in this contact event through coach and player education may be effective in reducing these injuries.